Sperm Heterogeneity Accounts for Sperm DNA Methylation Variations Observed in the Caput Epididymis, Independently From DNMT/TET Activities - Chen, Hong; Scott-Boyer, Marie-Pier; Droit, Arnaud; Robert, Claude; Belleannée, Clémence (Frontiers in Cell and Developmental Biology, 2022)
Following their production in the testis, spermatozoa enter the epididymis where they gain their motility and fertilizing abilities. This post-testicular maturation coincides with sperm epigenetic profile changes that influence progeny outcome. While recent studies highlighted the dynamics of small non-coding RNAs in maturing spermatozoa, little is known regarding sperm methylation changes and their impact at the post-fertilization level. Fluorescence-activated cell sorting (FACS) was used to purify spermatozoa from the testis and different epididymal segments (i.e. caput, corpus and cauda) of CAG/su9-DsRed2; Acr3-EGFP transgenic mice in order to map out sperm methylome dynamics. Reduced representation bisulfite sequencing (RRBS-Seq) performed on DNA from these respective sperm populations indicated that high methylation changes were observed between spermatozoa from the caput vs. testis with 5546 entries meeting our threshold values (q value < 0.01, methylation difference above 25%). Most of these changes were transitory during epididymal sperm maturation according to the low number of entries identified between spermatozoa from cauda vs. testis. According to enzymatic and sperm/epididymal fluid co-incubation assays, (de)methylases were not found responsible for these sperm methylation changes. Instead, we identified that a subpopulation of caput spermatozoa displayed distinct methylation marks that were susceptible to sperm DNAse treatment and accounted for the DNA methylation profile changes observed in the proximal epididymis. Our results support the paradigm that a fraction of caput spermatozoa has a higher propensity to bind extracellular DNA, a phenomenon responsible for the sperm methylome variations observed at the post-testicular level. Further investigating the degree of conservation of this sperm heterogeneity in human will eventually provide new considerations regarding sperm selection procedures used in fertility clinics.